Social Status Influence on Stigma Towards Mental Illness and Substance Use Disorder in the United States. - Miller, Paula K.; Cuthbertson, Courtney A.; Loveridge, Scott (Community Mental Health Journal, 2022)
We describe the relationship between socio-demographic membership and stigma towards any mental illness (AMI) and substance use disorder (SUD) in the United States using a national survey (N = 2512). We hypothesize that participants from higher status socio-demographic groups may be more likely to report stigmatizing attitudes than participants from lower status socio-demographic groups. We find support for our hypothesis using multiple linear regression. Participants who were college-educated, male, or had household incomes above the national median were more likely to report stigmatizing attitudes toward both AMI and SUD in comparison to participants that were not college-educated, were female, or had household incomes below the national median. In contrast to our hypothesis, we find that participants who identified as Hispanic were more likely to report stigmatizing attitudes toward AMI than non-Hispanic whites. Younger and urban participants were more likely to report stigmatizing attitudes than their older and non-urban counterparts.